2022
DOI: 10.1111/bjd.21274
|View full text |Cite
|
Sign up to set email alerts
|

Does the morphology of cutaneous melanoma help to explain the international differences in survival? Results from 1 578 482 adults diagnosed during 2000–2014 in 59 countries (CONCORD-3)

Abstract: Background CONCORD-3 highlighted wide disparities in population-based 5-year net survival for cutaneous melanoma during 2000-2014. Clinical evidence suggests marked international differences in the proportion of lethal acral and nodular subtypes of cutaneous melanoma. Objectives We aimed to assess whether the differences in morphology may explain global variation in survival. Methods Patients with melanoma were grouped into the following seven morphological categories: malignant melanoma, not otherwise specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…It is interesting that a large population-based cross-sectional analysis performed by Allais et al showed that the diagnosis of primary detected histologic subtype NM, corrected for Breslow thickness and ulceration, was associated with a decreased 5-year relative survival compared with SSM, suggesting that the histologic subtype should be taken into consideration in making treatment decisions [ 9 ]. In addition, a large international multi-center study, conducted by Di Carlo and colleagues, demonstrated similar results, with an increased hazard ratio for death in patients with NM (N = 5375) compared with SSM patients (N = 19.592), adjusted for sex, age, and disease stage at diagnosis [ 8 ].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It is interesting that a large population-based cross-sectional analysis performed by Allais et al showed that the diagnosis of primary detected histologic subtype NM, corrected for Breslow thickness and ulceration, was associated with a decreased 5-year relative survival compared with SSM, suggesting that the histologic subtype should be taken into consideration in making treatment decisions [ 9 ]. In addition, a large international multi-center study, conducted by Di Carlo and colleagues, demonstrated similar results, with an increased hazard ratio for death in patients with NM (N = 5375) compared with SSM patients (N = 19.592), adjusted for sex, age, and disease stage at diagnosis [ 8 ].…”
Section: Discussionmentioning
confidence: 85%
“…Molecular analysis shows that NM contains a lower mutational load compared with SSM, illustrating the distinct biologic molecular background [ 5 , 6 , 7 ]. Importantly, primary NM, even corrected for Breslow thickness and ulceration, is associated with lower overall survival and a reduced recurrence-free survival rate compared with primary SSM [ 8 , 9 , 10 ]. A retrospective study conducted by Lin et al in melanoma research suggested that the aggressiveness of NM is attributed to a decreased presence of tumor-infiltrating lymphocytes and an upregulation of PD-L1 expression in neoplastic cells compared with SSM; however the exact mechanism of the aggressive behavior of NM has not yet been unraveled.…”
Section: Introductionmentioning
confidence: 99%
“…Integrating these histopathologic findings with clinical information like the site of origin for tumors is important: acral (non-sun-exposed regions) and lentigo maligna melanomas both could have fusiform cells, but the prognoses are different, with thickness-matched acral melanoma being more aggressive (4). Moreover, prognosis varies by histologic subtype, where nodular and acral have generally worse outcomes than thickness-matched superficial spreading and desmoplastic subtypes (5,6). However, personalized prognostication of earlystage melanoma (< 0.75 mm) remains suboptimal.…”
Section: Introductionmentioning
confidence: 99%
“…2 ALM is very rare in northern hemisphere countries, accounting for <1% of the melanoma cases, but corresponds over 10% of cutaneous melanoma cases in Asia, Latin America, and Africa. 3,4 In Mexico, whose population is largely of mixed ethnicity, ALM comprises 44.1% of cutaneous melanoma, 5 whereas in Asia, 50-58% of cutaneous melanoma are ALM. 6 Acral lentiginous melanoma is the predominant histological subtype that occurs in acral, glabrous skin, such as sole, palms, and nail apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…This type of skin cancer can be classified into four major histologic subtypes: superficial spreading melanoma (SSM), which accounts for 70% of all melanomas in European‐descent individuals, nodular melanoma (NM), lentigo maligna melanoma (LLM), and acral lentiginous melanoma (ALM) 2 . ALM is very rare in northern hemisphere countries, accounting for <1% of the melanoma cases, but corresponds over 10% of cutaneous melanoma cases in Asia, Latin America, and Africa 3,4 . In Mexico, whose population is largely of mixed ethnicity, ALM comprises 44.1% of cutaneous melanoma, 5 whereas in Asia, 50–58% of cutaneous melanoma are ALM 6 …”
Section: Introductionmentioning
confidence: 99%